Deep Penetration of Pharmaceuticals and Personal Care Products through the Vadose Zone of Effluent‐Irrigated Land. Issue 1 (27th January 2015) - Zentner, Eitan; Gerstl, Zev; Weisbrod, Noam; Lev, Ovadia; Pankratov, Irena; Russo, David; Gasser, Guy; Voloshenko-Rosin, Anna; Ronen, Daniel
Abstract : Six boreholes were drilled during the course of a year to a depth of 2 m beneath the water table, located at a depth of about 28 m, under agricultural land sprinkler irrigated with treated sewage effluents in the Coastal Plain aquifer of Israel to determine the extent of penetration of 20 pharmaceuticals and personal care products (PPCPs) into the unsaturated zone. The fields were planted to turf and had different histories of effluent irrigation. From each borehole, 7 to 21 samples were taken for analysis of PPCPs, as was the underlying groundwater. Nine PPCPs (carbamazepine and its metabolite 10‐hydroxy‐10, 11‐dihydrocarbamazepine, acridone and acridine, venlafaxine, sulfamethoxazole, oxcarbazepine, O ‐desmethylvenlafaxine, and caffeine) were detected in the vadose zone of the study area to a depth of 27 m. For example, the detected concentrations of carbamazepine were up to 109 ng/kg, of caffeine up to 36, 700 ng/kg, and of venlafaxine up to 50 ng/kg. Only five of the compounds (carbamazepine, acridone, venlafaxine, sulfamethoxazole, and caffeine) were found in the underlying groundwater with concentrations in the nanogram per liter range. The results of this work show that significant amounts of PPCPs can penetrate even a thick vadose zone of 27 m with sections containing up to 50% clay and up to 0.40% soil organic C. Venlafaxine, for example, penetrated the vadose zone at an average velocity of 2.8 to 4 m/yr. Irrigation with treated sewage effluents or contaminated water should be carefully considered if the penetration of PPCPs into groundwater is undesirable.